Odpowiedzi

2009-12-14T17:33:15+01:00
2(x+y)-3(x-2y)=-7x-2
5(x+1)-2(3-y)=-4(x+y)

2x + 2y - 3x + 6y = -7x - 2
5x + 5 - 6 + 2y = -4x - 4y

2x + 2y - 3x + 6y + 7x = -2
5x + 2y + 4x + 4y = 6 - 5

6x + 8y = -2 |*3
9x + 6y = 1 *(-2)

18x + 24y = -6
-18x - 12y = -2

12y = -8 |:12
y = -1,5

18x + 24y = -6
18x = -6 - 24*(-1,5)
18x = -6 - (- 36)
18x = -6 + 36
18x = 30 |:18
x = 1,67



4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x + 8 - 3y + 3 = x + y - 3
3x - 12 - 2y + 4 = 4x - 4y + 4

4x - 3y - x - y = -3 - 8 - 3
3x - 2y - 4x + 4y = 4 + 12 - 4

3x - 4y = -14
-x + 2y = 12 |*3

3x - 4y = -14
-3x + 6y = 36

2y = 22 |:2
y = 11

-x + 2y = 12
-x = 12 - 2*11
-x = 12 - 22
-x = -10
x = 10
2009-12-14T17:36:54+01:00
Wychodzą mi bardzo dziwne wyniki coś chyba pomieszałam ... ;p
Więc sorka ale ta wyżej pewnie ma dobrze ;p ;]